Empowering Women’s Social Entrepreneurship In Aviation Through Halal Logistics Value Creation (HLVC) - Rohafiz Sabar; Nur Khairiel Anuar; Hasrul Hashom (Penerbit USIM, 2025)
International Halal Management Conference (IHMC) : “Empowering Halal Industry Towards Globalization” / Editor :-Farah Laili Muda @ Ismail, Nur Ainna Ramli & Anita Ismail Organized by Faculty of Economics & Muamalat, Universiti Sains Islam Malaysia 9 September 2025